Synthesis and Thermal Characteristics of N-(Thiazol-2-yl)methacrylamide-Acrylonitrile Copolymers - El-Hamouly, S.H.; Azab, M.M.; Diab, A.S.M.; Hegazy, M.A. (Asian Journal of Chemistry, 2011)
N-(Thiazol-2-yl)methacrylamide monomer has been prepared by the reaction of 2-aminothiazole either with methacryloyl chloride in the presence of triethylamine as catalyst or with methacrylic acid in the presence of N,N-dicyclohexyl carbodiimide as a dehydrating agent. The prepared monomer was copolymerized with acrylonitrile in dimethyl formamide using azobisisobutyronitrile as initiator. The homo-polymer and also the copolymers were characterized by a variety of spectral and thermal methods. The thermal behaviour in nitrogen of the homopolymer as well as the copolymers was investigated using thermogravimetric and differential thermal analysis techniques. N-(Thiazol-2-yl)methacrylamide was found to initiate the nitrile oligomerization in the copolymers upon heating. A mechanism for the degradation and initiation of the methacryloyloxy units in the nitrile copolymers is proposed. This was confirmed by interpreting the fragmentation patterns of the obtained mass spectra of the monomer, as well as the FT-IR spectra of the copolymers after heating.